The Latest in Vaccine Policies: Selected Issues in School Vaccinations, Healthcare Worker Vaccinations, and Pharmacist Vaccination Authority Laws. Issue 1 (2017) - Barraza, Leila; Schmit, Cason; Hoss, Aila
Abstract : This paper discusses recent changes to state legal frameworks for mandatory vaccination in the context of school and healthcare worker vaccination. It then discusses state laws that allow pharmacists the authority to vaccinate.